Analisis Faktor Maternal Terhadap Keluarga Berisiko Stunting Sebagai Upaya Peningkatan Analisis Data di BKKBN Kalimantan Timur - Rahmi Susanti (Jurnal Nasional Pengabdian Masyarakat, 2023)
According to Riskesdas 2018, the prevalence of stunting in East Borneo is 30%. Based on data from East Borneo's Health Office 2017 states that number of children under five years of age who are stunting relatively high, that is 30,6% of the total toodlers. Maternal factors are risk factors for stunting especially in the first 1000 days of life. The maternal factor is the risk of 4 Too. Too young, too old, too close and too many. The condition of 4T will increase risks in pregnancy including the risk of stunting, morbidity and even death of mother and baby. Objective: To analyze the correlation of maternal risk factors with families at risk of stunting in East Borneo Province. Method: this research used secondary data of 508,351 families on the PK21 tabulation report (recapitulation of families at risk of stunting). Data analysis used the Pearson Correlation test which first found that the data were normally distributed. Results: PK21 data shows that there are 79.% of families at risk of stunting. The distribution of maternal risk factors is too young 0.8%, too old 53.4%, too close 3.2% and too many 33.1%. And the results of the correlation analysis show that there is a correlation between maternal factors too young (0.001), too old (0.001), too close (0.001) and too many (0.001) with families at risk of stunting. Conclusion: The prevalence of stunting in East Borneo is quite high, so it requires prevention to reduce the maternal factor 4T rate.